Analisis Ushul Fiqh terhadap Lafaz Ditinjau dari Dilalah Al-Mantuq - DT, Kiki Reski Amalia; Fatmawati, Fatmawati; Abidin, Zaenal (An-Nahdloh: Journal of Education and Islamic Studies, 2025)
This study aims to analyze the concept of dilalah mantuq according to ushul fiqh and its role in establishing Islamic law. Mantuq is something that is designated by the pronunciation, and the pronunciation itself is an important part in legal istinbath because it can provide clarity and legal certainty regarding sharia provisions sourced from the Qur'an and Hadith. This study employs a descriptive qualitative method with a literature-based approach. Various works related to research are collected from multiple literary sources, including scientific journals, online articles, books, and other documents. The results of the study show that mantuq is divided into 3 parts, namely, sharih, ghairu sharih, zhahir, and mu'awwalah, each of which has its differences. This study explains that mantuq holds a central position in ushul fiqh, serving as the primary foundation for understanding lafaz nash and formulating Islamic law. Keywords: Dilalah, Mantuq, ushul fiqh